Synthesis and Spectral Studies of the Bivalent Transition Metal Complexes of 3-Hydroxypicolinamide - Lonibala, R.K.; Promila Devi, T.H.; Yumnam, Sharmeli; Babita Devi, R.K. (Asian Journal of Chemistry, 2010)
Some bivalent transition metal complexes of 3-hydroxypicolinamide (LH) of the empirical formulae, [M(LH)2Cl(H2O)]Cl [M = Mn, Co, Ni, Cd], [Cu(LH)2Cl(OH)], [Hg(LH)2Cl2] and [M(L)2(H2O)n] [M = Mn, Co, Ni, Cu, Cd, Hg] have been synthesized. 1H NMR studies suggested the presence of one dissociable proton in the ligand. IR and NMR data show that LH acts as a neutral N,O chelating ligand in the protonated form while it behaves as a uninegative O, O chelating species in the monodeprotonated form. Electronic spectral studies suggest distorted octahedral geometry for Mn(II), Co(II), Ni(II) and Cu(II) complexes. Isotropic nature of Mn(II) complexes and anisotropic nature of Cu(II) complexes at LNT have been inferred from the ESR studies. Appreciable covalent nature of bonding in the complexes is suggested by the bonding parameters obtained from electronic and ESR spectra. 113Cd chemical shift also shows that Cd(II) ion is covalently bonded in [Cd(LH)2Cl(H2O)]Cl. XRD powder patterns of the Cu(II) complexes are indexed for a tetragonal crystal system for [Cu(LH)2Cl(OH)] and orthorhombic for [Cu(L)2(H2O)2]. Tentative structures of these complexes have been suggested based on their elemental, thermal, molar conductance, magnetic moment, and spectral data.